Editorial "Art, Poetics and Visibility of People with Disabilities" (Revista de Ensino em Artes, Moda e Design, 2023)
Presentation of dossier 13 "Art, Poetics and Visibility of People with Disabilities", carried out by its organizers.
Keywords: art; poetic; visibility of people with disabilities